Protocol for screening cytotoxic activity of natural products against KB cells - Norhanom, A.W.; Ashril , K Awang, Y.; A. Hadi, A. Hamid (Malaysian Journal of Science, 1999)
In our studies on the anti-tumour bioassay on the human laryngeal carcinoma KB cell line, modifications were made to the protocol used by Institut de Chimie des Substances Naturelles (ICSN), Centre National de Ia Recherche Scientifique (CNRS) of Paris, France, to compensate for differences with respect to environment, type, concentration of chemicals and growth factors. In the preparation of the culture medium, sodium hydroxide was omitted, penicillin/streptomycin levels were doubled, and kanamycin was used at 50 IU mL-1. The tests were carried out in 4 mL culture media and each flask had 20,000 — 30,000 cells mUl. Adriblastine was used in the in vitro cytotoxicity test at 1 x 10-8 to 2.5 x 10-7 M; Neutral Red dye was used to detect cell damage. Our studies showed that the ED50 of adriblastine on KB cells was 0.1 x 10-7 to 0.3 x 10-7M.